2011
DOI: 10.2298/gensr1102407l
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nitrogen content in the needles of Douglas-fir (Pseudotsuga menziesii Mir/Franco) provenances

Abstract: Nitrogen content in the needles of twenty Douglas-fir provenances, originating from different sites within the native range of the species in the USA, was studied in a Douglas-fir provenance test established at the montane beech site on acid brown soil. Based on the variability of nitrogen content in the needles, the intensity and dynamics of the physiological processes of Douglas-fir mineral nutrition were analyzed as the indicators of Douglas-fir adaptive potential to the sites in Serbia. All the trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…Our analysis and some other foreign studies from Serbia, the Netherlands, and Bulgaria similarly confirm differences in growth among provenances [14,24,[44][45][46]. In our experiment, Yelm (1080) showed the best growth performance, it had the largest average dbh, and performed well against most other provenances (Table 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our analysis and some other foreign studies from Serbia, the Netherlands, and Bulgaria similarly confirm differences in growth among provenances [14,24,[44][45][46]. In our experiment, Yelm (1080) showed the best growth performance, it had the largest average dbh, and performed well against most other provenances (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Recent findings have revealed that several old Douglas-fir stands in Austria originated from areas outside the recommended regions (e.g., Northern California), indicating that additional seed sources may be suitable for Douglas-fir in Central Europe [28]. The provenance with the lowest average dbh in our trial was Merrit (1028), which originates from higher altitudes and latitudes in British Columbia; other provenances from these areas also grow poorly in Serbia [44] and Eastern Austria [49]. In contrast, in northern countries (e.g., the Netherlands), provenances from higher latitudes grow better, and growth decreases with decreasing geographical latitude of origin [24].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The Institute of Forestry in Belgrade has been carrying out provenance testing of Douglas-fir originating from Canada and America for more than 30 years (Lavadinović, V., et al, 2001, Lavadinović,V., et al 2011a, Lavadinović, S.,V., et al, 2011b, Lavadinović,V., et al 2011c, Lavadinović,V., et al, 2011d, Lavadinović,V., et al, 2014, Lavadinović, V., et al, 2015, Vera Lavadinović, et al, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…In Serbia, the study and the testing of Douglas-fir provenances from Canada and the United States of America has begun in 1978 at the Institute of Forestry, Belgrade, by setting up provenance trials on different sites (Lavadinović and Koprivica, 1996, 1996a, 1999Lavadinović and Isajev, 2005;Lavadinović, 2005;Lavadinović et al, 2010Lavadinović et al, , 2011Lavadinović et al, , 2015Lavadinović et al, , 2017Lavadinović et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%